Asante art and culture: the mainspring of Asante’s greatness and glory - Asiedu, Nana Kwaku (2011)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfillment of the requirements for the Degree of Master of Arts in African Art and Culture, 2005